PENERAPAN PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN NOMOR 51 TAHUN 2018 TENTANG SISTEM ZONASI PENERIMAAN PESERTA DIDIK BARU DI SMA N 3 SEMARANG - Supraptiyaningrum Supraptiyaningrum; Muzayanah Muzayanah (Jurnal Ilmiah Dinamika Hukum, 2020)
Every country has a purpose in carrying out the welfare of its people. The Indonesian state has the objectives as stated in the fourth paragraph of the preamble to the 1945 Constitution. One of them is to educate the nation's life. Educating the life of the nation aims to ensure that all Indonesians have the opportunity to receive education indiscriminately. Based on Law Number 20 of 2003, it is explained that the purpose of education is to develop the potential of students. The Ministry of Education and Culture issued a new regulation on PPDB, which is a zoning system that aims to create an education that is in line with the state's intent and equal access to services for students. Permendikbud Number 51 of 2018 divides into 3 pathways, namely zoning, achievement paths, and parent movement paths. The purpose of this study is to determine the zoning system regulations in Permendikbud No. 51 of 2019, to find out how the implementation of Permendikbud Number 51 of 2018 in SMA Negeri 3 Semarang, as well as the obstacles that occur and how the solutions are offered. The results of the research show that SMA Negeri 3 Semarang applies the applicable law by using the PPDB pathway, including zoning, achievement pathways, zoning achievement pathways, and also parents moving pathways. SMA Negeri 3 Semarang in implementing PPDB uses a zoning system, admitting that many high-achieving students are excluded. Thus, the Regional Government of Central Java gave the authority to SMA Negeri 3 Semarang to implement additional pathways, namely the achievement pathway, and the zoning achievement pathway, so that the zoning achievement and achievement pathways could minimize excluded students. Keywords: Zoning System, Implementation, Permendikbud.